210Pb numa região anômala de Pocinhos-Paraíba - Cleomacio Miguel da Silva; Crescêncio Andrade Silva Filho; Carlos Eduardo de Oliveira Costa Júnior (Brazilian Journal of Radiation Sciences, 2018)
From 1979 to 1982, the extinct company NUCLEBRAS carried out studies on the occurrence of uranium in Pocinhos, a city located in the harsh region of the State of Paraíba, where dairy farms currently exist. 210Pb, descending from the 238U radioactive series, is deposited in soil and plants, mainly due to the natural fallout of 222Rn. Once present in the plants, the 210Pb can be ingested by dairy cows, and then transferred to the milk. Thus, milk consumption may constitute an important route of 210Pb intake by man. In the human body, 210Pb is rapidly transferred to the bones, which can induce the onset of leukemia. In this context, the objective of the present work was to determine the concentrations of 210Pb in soil samples and forage palm (Opuntia spp.) From farms located in the uranium anomaly of the city of Pocinhos. For that, the ion exchange resin technique was used. The concentrations of 210Pb in the soil samples ranged from 7 to 5,098 Bq.kg-1. For the forage palm samples, the concentrations varied from 4 to 178 Bq.kg-1 in the dry matter. The results showed a high availability of 210Pb for the cattle feed chain of the farms studied.